Generation Z and the Future of the Accounting Profession: A Qualitative Study of Challenges and Adjustment in the Technology Era - INDRAJAYA, Anak Agung Ngurah Putra; ULANDEWI, Anak Agung Sagung Istri Rima; DEWI, Ni Kadek Shinta Yulia; TANAYA, Tjokorda Istri Agung Maheswari Putri (PT Batara Swastika Harati, 2024)
The digital transformation that has occurred in the world of accounting has given rise to fundamental changes in the roles and competencies required of an accountant. Generation Z, as the group that currently dominates higher education, is faced with the challenge of adapting to the dynamics of an increasingly technology-based profession. This study aims to understand how Generation Z accounting students view changes in the accounting profession and how they prepare themselves for the era of digitalization. This study uses a qualitative approach with a phenomenological study method. The subjects of the study were ten final-year accounting students selected through a purposive sampling technique. Data were collected through an open-ended questionnaire and analyzed thematically. The results showed that the majority of respondents had a positive attitude towards the digitalization of the accounting profession and realized the importance of mastering technology such as accounting software, cloud computing, and artificial intelligence. However, most respondents had not had direct experience with the technology and felt that learning on campus did not fully support their digital readiness. Within the framework of the Theory of Planned Behavior (TPB), it was found that students' positive attitudes and adaptive intentions had not fully developed into real behavior due to low perceptions of control over resources and weak social encouragement from the academic environment. This study recommends the need for stronger institutional support in the form of a curriculum that is responsive to technological developments and broader and more targeted access to training for students.